Inhibition of Wnt6 by Sfrp2 regulates adult cardiac progenitor cell differentiation by differential modulation of Wnt pathways. (August 2015) - Schmeckpeper, Jeffrey; Verma, Amanda; Yin, Lucy; Beigi, Farideh; Zhang, Lunan; Payne, Alan; Zhang, Zhiping; Pratt, Richard E.; Dzau, Victor J.; Mirotsou, Maria
Abstract: Wnt signaling has recently emerged as an important regulator of cardiac progenitor cell proliferation and differentiation, but the exact mechanisms by which Wnt signaling modulates these effects are not known. Understanding these mechanisms is essential for advancing our knowledge of cardiac progenitor cell biology and applying this knowledge to enhance cardiac therapy. Here, we explored the effects of Sfrp2, a canonical Wnt inhibitor, in adult cardiac progenitor cell (CPC) differentiation and investigated the molecular mechanisms involved. Our data show that Sfrp2 treatment can promote differentiation of CPCs after ischemia–reperfusion injury. Treatment of CPCs with Sfrp2 inhibited CPC proliferation and primed them for cardiac differentiation. Sfrp2 binding to Wnt6 and inhibition of Wnt6 canonical pathway was essential for the inhibition of CPC proliferation. This inhibition of Wnt6 canonical signaling by Sfrp2 was important for activation of the non-canonical Wnt/Planar Cell Polarity (PCP) pathway through JNK, which in turn induced expression of cardiac transcription factors and CPC differentiation. Taken together, these results demonstrate a novel role of Sfrp2 and Wnt6 in regulating the dynamic process of CPC proliferation and differentiation, as well as providing new insights into the mechanisms of Wnt signaling in cardiac differentiation. Highlights: Sfrp2 promotes CPC differentiation in vivo and in vitro. Sfrp2 inhibits CPC proliferation in vitro. Sfrp2 binds to Wnt6. Inhibition of Wnt6 by Sfrp2 activates JNK.